2008
DOI: 10.1016/j.physbeh.2007.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the serotonin reuptake transporter gene modify the consequences of social status on metabolic health in female rhesus monkeys

Abstract: Individuals vary substantially in their vulnerability to physical and psychosocial stressors. The causes of such variation in susceptibility to stress are poorly understood, but are thought to relate in part to genetic factors. The present study evaluated the extent to which polymorphisms in the gene encoding the serotonin reuptake transporter (5HTTLPR or SERT) modulated physiologic responses to the imposition of psychosocial stress (social reorganization and subordinate social status) in female rhesus monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(179 citation statements)
references
References 93 publications
(115 reference statements)
13
163
1
1
Order By: Relevance
“…This effect was further modulated by gender [57] . Short allele carriers of adult female rhesus monkeys subjected to social subordination showed increased plasma cortisol levels if being subordinate [58] . Moreover, these subordinate S-allele carriers also showed decreased negative feedback in the 0.25-mg DST.…”
Section: Genetic Variants In Neurotransmitter Systems and Hpa Axis Rementioning
confidence: 95%
“…This effect was further modulated by gender [57] . Short allele carriers of adult female rhesus monkeys subjected to social subordination showed increased plasma cortisol levels if being subordinate [58] . Moreover, these subordinate S-allele carriers also showed decreased negative feedback in the 0.25-mg DST.…”
Section: Genetic Variants In Neurotransmitter Systems and Hpa Axis Rementioning
confidence: 95%
“…There appeared to be an interaction with social status, genotype, and changes in serum concentrations of leptin and triiodiothyronine. Dominant LL-homozygote females had the highest levels while subordinate S-variant females had the lowest level (Jarrell et al 2008). Watson et al (2009) found that male rhesus Sallele carriers spent less time looking at the eye region of faces, and had larger pupil diameter when gazing at photographs of familiar highstatus males from the same cohort.…”
Section: Transporter Proteinsmentioning
confidence: 99%
“…It has also been shown that in depression carriers of the short variant benefit most from social support (Brummett et al 2008), indicating that sensitivity to positive stimuli can alleviate the negative consequences of sensitivity to adverse events. In a social context, short-allele carriers display more aggressive behaviours (Schwandt et al 2010) and are characterized by an increased vulnerability to the adverse effects of psychosocial stress associated with subordinate status (Jarrell et al 2008). An analogous attentional bias in rhesus monkeys is particularly striking: The short variant of the rh5-HTTLPR has been associated with a reduction in time spent gazing at images of faces compared to non-face images, less time looking in the eye regions of faces and larger pupil diameters when gazing at photos of a high versus low status male macaques (Watson et al 2009).…”
Section: Neural Mechanisms Of Epigenetic Programmingmentioning
confidence: 99%